PP140 Barriers And Prospects For The Development Of Hospital-Based Health Technology Assessment In Kazakhstan. (December 2021) - Avdeyev, Andrey; Benberin, Valeriy; Shanazarov, Nasrulla; Makalkina, Larissa; Kaptagayeva, Aigul; Akhmedullin, Ruslan; Hailey, David
Abstract : Introduction: The experience of implementing a hospital-based health technology assessment (HB-HTA) system in Kazakhstan is currently represented by only one organization, an independent HB-HTA unit established in 2015 in the Medical Center Hospital of the President's Affairs Administration (the Hospital). Despite the demonstrated positive experience of the Hospital, the widespread implementation of the HB-HTA system in Kazakhstan has experienced some barriers that must be considered before further development can occur. Methods: To determine the barriers to developing and implementing HB-HTA in Kazakhstani hospitals, data from the Hospital's experience were obtained through a survey of Kazakhstan hospitals, conducted on behalf of the Ministry of Health Care. An official response was received from 29 hospitals. During the survey and discussions with hospital staff using the "brainstorming" method, several barriers to the development of HB-HTA in Kazakhstan were identified. Results: Barriers at the system level included the lack of monitoring of the HB-HTA system at the national and regional levels and a lack of methodological support. Organizational barriers included a critically small number of HTA experts and the need for additional logistical support and funding from hospitals. The subjective factors we attributed to the rejection of the HB-HTA system by hospital management were the underestimation of lost profits and that HTA is a tool for promoting a transparent and open system for making managerial decisions. Conclusions: Despite some barriers, the development of HB-HTA in Kazakhstan is a promising area. The heads of key hospitals in Kazakhstan demonstrated a readiness and understanding of the need to use the principles of health technology assessment and clinical and economic analysis to promote the active transfer and implementation of innovative medical technologies.